The illusion of the One. Childhood as “Free Space” and Humor as a Vehicle for the Transcendent in Mario Levrero’s Narrative (2021)
We propose to analyze the role that humor plays in the work of the Uruguayan writer Mario Levrero. From the critical reading of stories from different moments of his career, we highlight that it is an indispensable resource for the construction of his poetic that allows him to delimit himself from the aesthetic presuppositions of what Ángel Rama (19) calls the critical generation. The Uruguayan conceives his writing as a therapeutic device and humoras a vehicle towards the transcendent. From a worldview that appropriates remains of romanticism, parapsychology and Jungian psychoanalysis, Levrero pursues in his texts access to the Spirit/Unconscious, an (im)possible path to the (self)knowledge. Literature then becomes a “free space” that associates with childhood, is realized in writing and is opposed to the alienated life of adults, in particular, that of the everyday self of the author, Jorge Varlotta.